Exploration of microbial resources for plant disease management - BHAGAT, SOMESHWAR (Indian Phytopathology, 2016)
Microbes are most important and precious resources which are naturally present in soil ecosystem. Microbes consist of several prokaryotic and eukaryotic microorganisms and are ubiquitously found in almost all ecosystem including agricultural soil, sea water, forest, etc. Trichoderma spp. and plant growth promoting rhizobacteria (PGPRs) are the most important microbes in plant disease management, which have been used most widely across the world. This paper highlights the major functions of biocontrol of Trichoderma spp and PGPRs, interaction of Trichoderma/PGPRs Plant Pathogens-Plant and their use in plant disease management. They have multifaceted function with intensive crop health care but need certain congenial conditions (presence of organic matter, soil moisture, temperature, pH, etc. for their maximum bioefficacy. The selection of superior strains of biocontrol agent, mass production and formulation technology (including products from BCA) and method of delivery in the field are the most crucial aspects in biocontrol of plant disease management.